2005
DOI: 10.1037/0021-843x.114.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-based subfactors of DSM-defined conduct disorder: Evidence for etiologic distinctions.

Abstract: Past research investigating the structure of conduct disorder (CD) symptoms has provided evidence of a phenotypic distinction between aggressive and rule-breaking subfactors of CD. However, evidence of etiologic distinctions between these subfactors has not been reported to date. In the current study, the authors investigated this issue in a sample of 1,151 male twins who were 17 years of age. The results indicate that aggressive and rule-breaking CD subfactors have both common and distinct etiologic influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
88
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 26 publications
7
88
1
Order By: Relevance
“…Meta-analytic studies (Rhee & Waldman, 2002) have concluded that genes influence 40%-50% of population variation in antisocial behavior, but the proportion is greater (60%-65%) for aggressive antisociality (Tackett, Krueger, Iacono, & McGue, 2005). Biological characteristics related to aggressive behavior may be the result of genetic variation.…”
Section: Etiological Factors: Genes and Family Environmentmentioning
confidence: 99%
“…Meta-analytic studies (Rhee & Waldman, 2002) have concluded that genes influence 40%-50% of population variation in antisocial behavior, but the proportion is greater (60%-65%) for aggressive antisociality (Tackett, Krueger, Iacono, & McGue, 2005). Biological characteristics related to aggressive behavior may be the result of genetic variation.…”
Section: Etiological Factors: Genes and Family Environmentmentioning
confidence: 99%
“…This distinction is evident in both empirically-derived behavioral rating scales, such as Achenbach's Child Behavior Checklist, and in factor analyses of DSM-defined conduct disorder symptoms (Tackett et al 2005;Tackett et al 2003). Moreover, subsequent studies have indicated that physical aggression (e.g., physically attacking others, bullying) and non-aggressive rule-breaking (e.g., lying, stealing without confrontation, vandalism) appear to have different developmental trajectories.…”
mentioning
confidence: 98%
“…Although conduct disorder is defined as a single category of mental disorder, its criteria delineate two dimensions with distinct etiologies (Tackett, Krueger, Sawyer, & Graetz, 2003). The first dimension reflects aggressive behavior and is influenced by genetic and person-specific environments, whereas the second dimension reflects delinquent and rule-breaking behavior and, in comparison with aggressive behavior, is relatively more influenced by shared familylevel environment factors (Tackett, Krueger, Iacono, & McGue, 2005). This phenotypic and etiologic distinction within the criteria for conduct disorder may reflect the distinction in the externalizing spectrum between the general externalizing factor (λ 1 ) and the aggressive subfactor (λ 2 ), a possibility that could be useful in framing future research and conceptions of conduct disorder.…”
Section: Advantages Of the Esmmentioning
confidence: 99%